128 What enables and constrains shared decision-making about opiates for people living with chronic breathlessness? A systematic narrative review and framework analysis of published data using a program theory of shared decision-making. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Licastro, Giovanna Impelliziere; Prihartadi, Aliya Syahreni; Pearson, Mark
Abstract : Background: Despite the evidence supporting the use of opioids to manage chronic breathlessness, these are rarely prescribed, indicating the need for enhanced SDM in this field. The Waldron 2020 SDM program theory explores the relationship between various factors in patients' and healthcare professionals' (HCPs) engagement in SDM. This systematic narrative literature review assesses enablers and constrainers of SDM in the prescription of opioids for chronic breathlessness and evaluates whether the Waldron'¯SDM program theory can explain the operation of these factors. Methods: A literature search was conducted on Medline, Embase, PsychInfo, Cochrane Database of Systematic Reviews, CINAHL, Scopus, and Web of Science (1946 '' June 2020). Studies were selected if they took place in Europe, Canada, or Oceania, and addressed an element present in decision making for the management of chronic breathlessness with opioids. Thematic analysis identified patient and HCP factors involved in the prescribing of opioids for chronic breathlessness. Their effect on SDM was assessed using Waldron's SDM programme theory. Results: Six themes were identified: concerns with side effects, knowledge of opioid use for breathlessness, acceptability, prior experiences, awareness of symptom severity, and system support. HCPs were reported to have more negative attitudes towards opioid use for breathlessness, particularly in the context of COPD, than patients. HCP's support by the MDT improved engagement in SDM. Open, clear communication addressing patients' questions and concerns, alongside HCP's revisiting of the discussion enabled SDM. A simple change in attitude from either the patient or HCP could be determining to increasing engagement with SDM. Conclusions: Research is scarce on SDM in opioid prescription for breathlessness. Limitations include the lack of quality appraisal of evidence. The Waldron SDM program theory appropriately supports SDM in this context. This review informs patient-centred care on management of chronic breathlessness with opioids through SDM, and highlights gaps in the literature.